A Versatile Prodrug Strategy to In Situ Encapsulate Drugs in MOF Nanocarriers: A Case of Cytarabine‐IR820 Prodrug Encapsulated ZIF‐8 toward Chemo‐Photothermal Therapy. (1st July 2018) - Zhang, Huiyuan; Li, Qian; Liu, Ruiling; Zhang, Xinke; Li, Zhonghao; Luan, Yuxia
Abstract: Zeolitic imidazolate framework‐8 (ZIF‐8) is an attractive metal organic framework (MOF) in drug delivery. Strong interaction between drugs and ZIF‐8 is essential for high drug loadings through in situ construction of MOFs. However, only limited drugs with unique functional groups (COOH, SO3 H, et al.) can interact with ZIF‐8 and be encapsulated satisfactorily so far. Drugs without these functional groups are difficult to be loaded due to the lack of strong interaction. Herein a versatile prodrug strategy is proposed to solve the problems encountered by MOFs. Cytarabine (Ara) is chosen as a model drug since it cannot be loaded in ZIF‐8 satisfactorily by itself. New indocyanine green (IR820) is utilized to bond with Ara for the formation of prodrug (Ara‐IR820) and endows the prodrug with fluorescence imaging‐guided chemo‐photothermal therapy, in which sulfonic groups strengthen the interaction between prodrug and ZIF‐8. This prodrug loaded ZIF‐8 is further functionalized with hyaluronic acid (HA) to result in active‐targeting HA/Ara‐IR820@ZIF‐8 nanoparticles. The in vitro and in vivo results demonstrate its excellent visual cancer therapy with tumor‐targeted and pH‐responsive release behavior. This design offers a new concept to solve the drug loading problem of MOFs, exhibiting a flexible strategy to expand the biomedical applications of MOFs. Abstract : A versatile prodrug strategy is proposed to solve the drug loading problems for drugs without strong interaction with metal organic frameworks (MOFs). The HA/Ara‐IR820@ZIF‐8 is smartly designed to overcome the limitation of MOFs on drug loading by the "dragging effect" from the functional group in prodrug, endowing MOFs as universal drug nanocarriers toward excellent chemo‐photothermal therapy.